Room temperature lithium superionic conductivity in high entropy oxides. Issue 24 (2nd June 2016) - Bérardan, D.; Franger, S.; Meena, A. K.; Dragoe, N.
Abstract : Impedance spectroscopy measurements evidence superionic Li + mobility (>10 −3 S cm −1 ) at room temperature and fast ionic mobility for Na + (5 × 10 −6 S cm −1 ) in high entropy oxides, a new family of oxide-based materials with the general formula (MgCoNiCuZn)1− x − y Ga y A x O (with A = Li, Na, K). Abstract : Impedance spectroscopy measurements evidence superionic Li + mobility (>10 −3 S cm −1 ) at room temperature and fast ionic mobility for Na + (5 × 10 −6 S cm −1 ) in high entropy oxides, a new family of oxide-based materials with the general formula (MgCoNiCuZn)1− x − y Ga y A x O (with A = Li, Na, K). Structural investigations indicate that the conduction path probably involves oxygen vacancies.